EFFECT OF RASNA TAILA MATRA BASTI IN LUMBAR SPONDYLOSIS - Sarmah, *Nibedita; Baishya, Anup (International Journal of Ayurveda and Pharma Research, 2017)
Lumbar spondylosis or osteoarthritis of spine is one of the most common types of arthritis where patient complain of back pain that increases with movement and associated with stiffness. Due to the hyaline articular cartilage loss and its disordered repair resulting increased thickness and sclerosis of the subchondral bony plate and overgrowth of bony substances at joint margin which is known as osteophyte. Vertebral column is the Asthi dhatu in Ayurveda. Panchabhautik composition of Asthi dhatu is Prithvi, Vayu and Akash. Vata dosha dusti leads to Asthi dhatu kshaya and Asthi kshaya may leads to Vata vriddhi. This is known as Ashraya ashrayee bhava of Asthi dhatu and Vayu. So, to treat the Asthi kshayaja vyadhi i.e. lumbar spondylosis, Vata pacifying measures will be helpful. Keeping that view in mind Rasna taila which has Vata samak and Brimhaniya (nourishing) property was selected as Matrabasti to use in 15 number patient of lumbar spondylosis in the dose of 60 ml. No any other medication was allowed orally or through any other route during trial period and efficacy of the therapy was observed on the basis of subjective and objective parameters. In all the parameter result was highly significant i.e. p<0.001. This observation helps us to consider lumbar spondylosis as a Dhatukshayaja vata vyadhi.